Generation Y and Z's Preferences on Intentions to Use Halal Products for Daily Dental and Oral Care - Permasari Sabaniah; Indra; Achmad Firdaus (International Journal of Economics (IJEC), 2024)
Background: Even if global economic growth is modest, Indonesia's halal business presents a tremendous chance to help the country's development. In general, the worldwide market, including the pharmaceutical and cosmetics industries, must address the need for halal products. Objective: This study intends to determine whether attitudes, subjective norms, behavioral control, and religion influence the intention to use halal oral health care items on a daily basis on Y and Z generation. These products are widely used but the study is still limited. Behavioral control, religion, and subjective norms were found to influence the intention or intent to use, as determined by this study. On the other side, there is no substantial relationship between attitude and intent to use. Research Method: Methods of data analysis in this research using Structural Equation Modelling (SEM). Sample of research used in this study is 146 respondent. The data used in this research is primary data sourced from generation Y and Z in IndonesiFindings: This research will help halal industry participants, particularly the pharmaceutical and cosmetic sub-sectors, develop strategies to boost public product knowledge and consumption. In addition, this research will serve as a reference for regulators working to improve the halal industry environment, including regulation and infrastructure.